Street vendor entrepreneurship development system for local community, the case study from Southern Thailand - Awapak, Yuwasri; Un-ob, Praphaphan; Boribanbunpotkate, Saksri; Bunmak, Suttiporn (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the street vendor’s entrepreneurship landscape and its development system based on a case study from Southern Thailand, using a mixed-methods methodology. There were 68 participants altogether, besides quantitative surveys with vendors, 19 in-depth interviews were conducted with stakeholders, including local practitioners and experts. Guided by the Entrepreneurship System (EDS) and system thinking frameworks, the findings reveal that street vendor participants exhibit a high level of entrepreneurial traits (X̅= 2.62, SD = 0.24), with self-confidence and commitment as the most prominent characteristics, while problem-solving, negotiation, and networking were identified as core entrepreneurial skills. Digital marketing was highlighted as critical skills which require further development. The analysis identified four interrelated components of the entrepreneurship development system as follows: 1) operational goals; 2) implementing organizations and agencies; 3) entrepreneurial skills development strategies; and 4) resource support mechanisms. The conclusion highlights the importance of tailored, inclusive, and collaborative framework which could be adapted and applied in similar contexts. Specific recommendations for policymakers, local governments, and street vendors are provided to guide the design, implementation, and continuous improvement of the system that empowers street vendors as well as strengthens local community economy and livelihoods.